2020
DOI: 10.1136/bmjdrc-2020-001468
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes status and dietary intake modify maternal and cord blood allostatic load markers

Abstract: IntroductionAllostatic load (AL) defines cardiometabolic, inflammatory, and neuroendocrine changes in the body in response to internal and external stressors. It is largely unknown whether gestational diabetes mellitus (GDM) alters maternal and fetal AL, which in turn affects GDM outcomes. Whether dietary intakes and quality can modify AL and thus influence GDM progression is also unknown.Research design and methodsIn this study, we recruited 35 GDM and 30 non-GDM women in gestational week 25–33. Fasting blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Ultimately, 15 articles were included. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The literature screening process and the results are shown in Figure 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Ultimately, 15 articles were included. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The literature screening process and the results are shown in Figure 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Our null findings are in line with some prior reports. 25,27,28,30 For example, a prior study including 54 mother-child pairs 31 found that maternal fasting glucose levels were not associated with child salivary cortisol reactivity in response to the Marshmallow Test, which is a test of delayed satisfaction that may be used to induce mild stress in young children. Our results are also consistent with a prior study of adverse maternal metabolic conditions which found that GDM was not associated with cord blood cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, few human studies have assessed offspring cortisol levels in the context of exposure to GDM or maternal hyperglycemia. [25][26][27][28][29][30][31] Furthermore, results of prior studies have been conflicting and have primarily been conducted in small cohorts. [25][26][27][28][29][30][31] Additionally, some of them have not accounted for potential confounding, such as maternal body mass index (BMI) and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations